Global Challenges for Business and Entrepreneurship: Case of Oman - Matriano, Maria Teresa (Advances in Social Sciences Research Journal, 2022)
Globalization has created various challenges among businesses and entrepreneurs. For many years, businesses have been facing challenges, such as increased competition, financial issues, and other operational challenges. Accordingly, businesses and entrepreneurs must adopt new strategies to address these emerging global challenges to remain competitive in the industry where they belong. Hence, it is also essential for entrepreneurs to employ strategic decision-making to achieve success within a business environment that is facing multiple global challenges. The goal of this study is to explore the current global challenges being faced by businesses and entrepreneurs, especially in the case of Oman. Some of the identified challenges for businesses and entrepreneurship includes keeping up with the current trends in business, global market competition, economic issues, information and communication technology (ICT) challenges, the current global health crisis, and other business-related issues. The variations of the global challenges must be understood properly by businesses and entrepreneurs to ensure business competitiveness, despite the risk of unwanted business outcomes brought by these challenges. With the emergence of these challenges, business owners or entrepreneurs will also have the chance to develop their strategic decision-making and even develop new strategies that will help the business survive.